Determinants of Reproductive Health Services Needs for Brides and Grooms in Brebes District - Silfia Addina; Sri Achadi Nugraheni; Sutopo Patria Jati (Jurnal Kebijakan Kesehatan Indonesia, 2020)
The utilization of reproductive health services for brides and grooms is still far from the national target (80%), that is 15.8%. This service is deemed lacking in meeting the needs of the bride and groom with various factors. This study aims to analyze the factors that influence the need for reproductive health services for the brides in Brebes District. This research method is quantitative observational research with cross-sectional approach. The population of this research is all brides who have registered in all Religious Affairs Office in Brebes District are 528 people. Primary data were collected through interviews using a structured questionnaire with 165 respondents selected through cluster sampling techniques. Bivariate data analysis was performed by Chi-Square test and multivariate data analysis was performed by logistic regression test. The results of this study indicate that there is a relationship between sex, knowledge, norms and culture of the community, and service technology (p-value <0.05) with the reproductive health service needs for brides and grooms. Meanwhile, the level of education, attitudes, and risk factors are not related to the reproductive health service needs for brides and grooms (p-value> 0.05). The strongest factor affecting the reproductive health service needs for brides and grooms is knowledge (OR = 2.736, 95% CI = 1,383-5,414). The recommendations of this study are service providers conducting surveys and needs for reproductive health services for brides and grooms continuously, branding by involving community leaders and health cadres, and the use of service technology that is practical, interesting and not boring, and can be accessed wherever and whenever they are.